2012
DOI: 10.1016/j.kjms.2011.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Severity of fatty liver on ultrasound correlates with metabolic and cardiovascular risk

Abstract: Non-alcoholic fatty liver disease is associated with an increased risk of metabolic and cardiovascular diseases. Whether the severity of fatty liver on ultrasound correlates with metabolic or cardiovascular risk remains unclear. A total of 1000 people receiving health examinations were enrolled, and 126 were excluded due to the presence of HBsAg, anti-HCV, known hepatic disorders or alcohol use (>140 g/wk). Significant fatty liver consisted of moderate and severe fatty liver on ultrasound. The definition of ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 45 publications
2
10
0
Order By: Relevance
“…A total of 271 consecutive children were enrolled in this study and all parents gave written informed consent. During the initial investigations, liver fat was identified by ultrasonography using established criteria, a bright hepatic echo pattern compared to echo response of the right kidney . Other causes of steatosis, were excluded, such as total parenteral nutrition, use of drugs known to induce steatosis (eg valproate, amiodarone or prednisone), viral hepatitis (A, B, C, Cytomegalovirus and Epstein‐Barr virus), autoimmune or metabolic liver diseases, alpha‐1‐antitrypsin deficiency, Wilson's disease, and celiac disease.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 271 consecutive children were enrolled in this study and all parents gave written informed consent. During the initial investigations, liver fat was identified by ultrasonography using established criteria, a bright hepatic echo pattern compared to echo response of the right kidney . Other causes of steatosis, were excluded, such as total parenteral nutrition, use of drugs known to induce steatosis (eg valproate, amiodarone or prednisone), viral hepatitis (A, B, C, Cytomegalovirus and Epstein‐Barr virus), autoimmune or metabolic liver diseases, alpha‐1‐antitrypsin deficiency, Wilson's disease, and celiac disease.…”
Section: Methodsmentioning
confidence: 99%
“…During the initial investigations, liver fat was identified by ultrasonography using established criteria, a bright hepatic echo pattern compared to echo response of the right kidney. 14…”
Section: Anthropometrical and Biochemical Measurementsmentioning
confidence: 99%
“…Overweight/obese children and adolescents (defined by body mass index (BMI) with NAFLD, who were referred to the "Hepatometabolic Department" of the "Bambino Gesù" Children's Hospital, from January 2012 to November 2014 provided the data for the current study. In all patients, liver fat was initially identified by ultrasonography using established criteria, a bright hepatic echo pattern compared to echo response of the right kidney [11].Other causes of steatosis, were excluded in all subjects, including alcohol intake (≥ 140 g/week), total parenteral nutrition, and the use of drugs known to induce steatosis (e.g. valproate, amiodarone or prednisone).…”
Section: Anthropometrical and Biochemical Measurementsmentioning
confidence: 99%
“…Fructose is absorbed in the intestinal lumen, and is then transported to the liver, where it rapidly enters glycolysis and is phosphorylated to fructose-1-phosphate by KHK. The phosphorylation of fructose also stimulates adenosine monophosphate (AMP) deaminase to convert AMP in inosine monophosphate (IMP) and then IMP is converted to uric acid [11]. Patients with NAFLD, who have a history of high fructose exposure, have a high concentration of UA, because they show a higher hepatic ATP depletion in response to fructose.…”
Section: Histological Features Of Nafldmentioning
confidence: 99%
“…3 Our previous studies on Taiwanese NAFLD patients showed that serum ALT level is positively associated with carotid atherosclerosis 4 and the severity of hepatic steatosis on ultrasonography could stratify CVD risk estimated by Framingham risk score. 5 Taking these lines of evidence together, serum ALT level and the severity of hepatic steatosis on ultrasonography could serve as surrogate markers of CVD risk in patients with NAFLD. Second, recent studies have identified genetic factors associated with NAFLD.…”
mentioning
confidence: 99%